Topical Application of M89PF Containing Vichy Mineralising Water and Probiotic Fractions Prevents Cutaneous Damage Induced by Exposure to UV and O3 - Benedusi M; Kerob D; Guiotto A; Cervellati F; Ferrara F; Pambianchi E (Dove Medical Press, 2023)
Mascia Benedusi,1 Delphine Kerob,2 Anna Guiotto,3 Franco Cervellati,1 Francesca Ferrara,4 Erika Pambianchi5 1Department of Neuroscience and Rehabilitation, University of Ferrara, Ferrara, Italy; 2L'Oreal Dermatological Beauty, Levallois, France; 3Department of Environmental Sciences and Prevention, University of Ferrara, Ferrara, Italy; 4Department of Chemical, Pharmaceutical and Agricultural Sciences, University of Ferrara, Ferrara, Italy; 5North Carolina Research Campus, Plants for Human Health Institute, Animal Science, North Carolina State University, Kannapolis, NC, 28081, USACorrespondence: Mascia Benedusi, Department of Neuroscience and Rehabilitation, University of Ferrara, via Borsari 46, Ferrara, 44121, Italy, Tel +390532455462, Email bndmsc@unife.itPurpose: Exposure of the skin to ultraviolet radiation (UV) or ozone (O3) results in stressed skin, leading to the alteration of the skin physical barrier and defence functions. In this work, the preventive benefit of a dermocosmetic, M89PF, containing Vichy mineralising water, probiotic fractions, antioxidant vitamins and hyaluronic acid, in the alteration of skin physical barrier and skin defence functions after exposure to O3 and UV, alone or combined, was assessed.Methods: Untreated and treated (M89PF) skin explants were exposed to O3, to UV rays or to O3+UV. Immunofluorescence was performed for skin barrier, oxidative stress, and inflammatory markers after one and four days of exposure to the pollutants.Results: M89PF significantly (p≤ 0.05) prevented the decrease of the expression level of different skin barrier markers, and significantly (p≤ 0.05) prevented the induction of OxInflammatory markers and inflammasome components by UV, O3, or both combined.Conclusion: M89PF prevents skin barrier damage, as well as oxidative stress and inflammatory markers induced by exposome factors, such as UV, O3, or both combined.Keywords: ultraviolet radiation, ozone, skin barrier, oxidative stress, inflammation